The Jungian Journey: Transcending Trauma and Reclaiming the Soul in Margaret Atwood’s Lady Oracle and Hilary Mantel’s Beyond Black - Hufstetler, Marlana Dian (My University, 2024)
Trauma transcendence is a common theme within Margaret Atwood and Hilary Mantel’s works, and it is also an important steppingstone in achieving Soul reclamation. From a Jungian perspective, the Soul and the Self are two terms often used interchangeably, both describing “the totality of the whole psyche” (Jung and von Franz, Man and His Symbols 161). Soul reclamation happens when an individual becomes one with their full identity, exploring and accepting all the parts of the psyche as one. During this process, an individual partakes in a mystical journey of sorts through a process of individuation. This thesis, “The Jungian Journey: Transcending Trauma and Reclaiming the Soul in Margaret Atwood’s Lady Oracle and Hilary Mantel’s Beyond Black,” follows the Jungian journey of Soul reclamation after trauma within a metaphysical context. Written only decades apart, both novels portray two very lost women with strong ties to the mystical. By exposing the Jungian archetypes of Persona, Shadow, and Animus within the female protagonists of Lady Oracle and Beyond Black, trauma theory can be applied in a way that exposes the psyche’s relationship to the metaphysical along with how this relationship determines the failure or completion of the journey to the Soul.
Keywords: Academic theses; Literature; Literature—History and criticism; Jungian psychology; Psychic trauma in literature; Atwood, Margaret, 1939—Criticism and interpretation; Mantel, Hilary, 1952—Criticism and interpretation; Atwood, Margaret. Lady Oracle; Mantel, Hilary. Beyond Black